Beef cattle production in the United States: a complex matrix of interconnected nutritional, health, and welfare management practices - Simroth Rodriguez, Jorge Carlos (Kansas State University, 2018)
With the concerning predicted growth of the world population for the next decades it is evident that farmers, ranchers, and cattle feeders need to find alternative ways to increase food production globally and assure food provision for future generations. The United States has an impressive reputation in global beef production. Beef cattle production in the United States is a complex industry with thousands of operations differing in geographical location, environmental conditions, management practices, operative systems, feedstuffs used, type of cattle raised or fed, production type, cattle capacity, and design of facilities. Beef cattle feeding operations exist all across the United States, but the majority of the larger feedlot operations are located in the Great Plains region. Feeding cattle is considered a high-risk business driving cattle feeders to implement all technologies available with best management practices with the goal of improving sustainability and profitability of their operations through biological and economical efficiencies. Thus, it is theorized that profitability in the feedlot industry is achieved when cattle feeders meet the requirements of the basic production management factors, such as cattle health, nutrition, and welfare in an equilibrated fashion. The first objective of this research was to describe recommended practices made by veterinary consultants and practitioners who service clients with commercial beef cow-calf operations in the US and Canada in terms of vaccine protocols, health practices, and production practices to establish a benchmark for standard operating procedures used in the beef cattle industry. The second objective of this research was to provide a thorough description of outdoor cattle feeding facilities currently being used by feedlots in the High Plains region of the United States that would serve as a benchmark for those looking to build a new facility or enhance an existing cattle feedlot. The third objective of this research was to obtain descriptive data regarding feedlot cattle management practices and cattle health and use it as a tool to make comparisons of cattle management practices between feedlots that might explain the difference in AIP incidence between feedlots in multiple locations. The fourth objective of this research was to evaluate the effects of periodic feeding of low-quality long-stemmed roughage in Holstein steers fed a steam-flaked corn-based finishing diet on dry-matter intake, ruminal dynamics, ruminal fermentation parameters, and fecal starch concentration.
Keywords: Cattle; Feedlot; Nutrition; Health; WelfareBeef